IMPLEMENTASI SISTEM AKUNTANSI DENGAN APLIKASI ACCURATE ACCOUNTING (STUDI KASUS CV. INDAH RASA FOOD COURT TANJUNGPINANG) - Fauzi Fauzi; Tikaria Tikaria; Marina Lidya (Bajang Institute, 2023)
This study aims to determine the application of the accounting system in CV. Indah Rasa Food Court, to find out the application of the CV accounting system. Indah Rasa Food Court by using the Accurate Accounting application. The results of this study are the financial records of CV. So far, Indah Ras Food Court Tanjungpinang has only kept simple financial records in the form of date information, transaction information, and amount. This is caused by the lack of understanding of the CV owner. Indah Ras Food Court Tanjungpinang to prepare financial reports in accordance with accounting principles. Recording of financial transactions CV. Indah Ras Food Court Tanjungpinang after being compiled using the Accurate Accounting application becomes more automated and already has an accounting system such as forms, journals, ledgers and financial reports in the form of income statements and balance sheets, so that CV. Indah Rasa Tanjungpinang Food Court can see the general financial condition of the business.